Developing Motor Skills through Dance - Ivančič, Gabrijela (Širjenje obzorij o poučevanju glasbe, 2025)
Dance as an activity significantly contributes to the development of children's motor skills by enhancing coordination, balance, flexibility, and precision of movement. This chapter underscores the importance of dance as a tool for holistic development, encompassing physical, emotional, and social growth. Research indicates that dance activities, which involve the synchronization of movements and rhythm, positively influence children's physical fitness and increase their motivation to engage in physical activity. Furthermore, dance enhances social skills, self-confidence, and teamwork. Music accompanying dance serves as both motivation and inspiration, creating a positive atmosphere and fostering a deeper understanding of the connection between sound and movement. The aim of this chapter is to highlight the role of dance in promoting children's health and development, as well as the importance of integrating dance activities into the educational process.